O083 A proof of principle study of cell targeted delivery of sirna guided by innate repair receptor epor/βcr highly expressed by injured tubular epithelial cells in porcine kidneys subjected to extended cold ischaemia times. (22nd July 2022) - Black, J; Cox, M; Chung, W; Lowe, M; Barber, J; Dennison, AR; Bagul, A; Yang, B
Abstract: Introduction: Small interfering RNA (siRNA) has been used in biological models for disease modification. Whilst challenges remain with targeted cell delivery, caspase-3, an executing enzyme of apoptosis and inflammation, plays a crucial role in acute kidney injury. Using caspase-3 siRNA or erythropoietin derived peptide CHBP, we have demonstrated renoprotection against ischaemia-reperfusion injury in isolated kidney preservation, and further applied the conjugate of both. Methods: Porcine kidneys (n = 3) subjected to 10 minutes of warm ischemia were retrieved and perfused with 500 mL hyperosmolar citrate. In comparison with the control (Kidney 1) caspase-3 siRNAHBSP (Kidney 2) or CHBP (Kidney 3) conjugate was administered into the kidney and autologous blood and stored for 22 hours in ice. Organs were then preserved by normothermic perfusion (NP) for 3 hours using clinical-grade cardiopulmonary bypass. Functional parameters were recorded, and kidney biopsies were taken at time zero (pre-perfusion) and hourly intervals following NP. Results: Preliminary findings showed increased arterial flow rate and urine output together with neutralised perfusate pH in the kidneys (2 and 3) receiving both conjugates compared to the control. Conclusion: Improved physiological outcomes in kidneys subjected to the novel agent treatment suggest protective effects against ischaemia. We hypothesise outcomes should be transferrable to human kidneys, which may facilitate the use of marginal kidneys following prolonged ischaemia, otherwise deemed unsuitable for transplantation. Renal histological and molecular studies of the effect of the agent are underway. Take-home message: Despite a small sample, this pilot proof of principle study suggests that caspase-3 inhibitors may have a role in limiting the detrimental effects of ischaemia on renal tissues subjected to prolonged cold ischaemic times. It is hoped that this may be beneficial if replicated in the human kidney model at increasing the deceased donor organ pool by enabling use of marginal kidneys subjected to prolonged ischaemic times.